Understanding adoption of conservation agriculture practices in Southern Africa: insights from household and community surveys and their implication for scaling: a synthesis report understanding and enhancing the adoption of conservation Agriculture in Smallholder Farming Systems of Southern Africa (ACASA) project - Chikoye, D.; Alene, A.; Hirpa Tufa, A.; Ngoma, H.; Marenya, P.; Thierfelder, C. (International Institute of Tropical Agriculture, 2024)
The need for resilient transformation of agri-food systems is an urgent issue in global development. This transformation must start from primary production by reducing the land, water, and climate footprint of production systems. This is true in Southern Africa as well. For close to three decades, conservation agriculture (CA) has been proposed as one way to combat climate change and resource degradation, reduce drudgery, and enhance the productivity of smallholder farming systems, especially in resource-poor and agroecologically challenging environments. Yet, the benefits of CA to society require that the practice is adopted on a wide scale. Evidence from agronomic and biophysical research at agricultural research stations and on farmers’ fields have shown the potential benefits of CA in improving soil health and yields (especially in the longer term). Commendably, many farmers in southern Africa are increasingly becoming aware of CA. Indeed, more than 90% of the household representatives who participated in this study indicated that they were aware of conservation agriculture. Yet, the adoption of novel CA methods such as direct seeding, ripline tillage, and mulching is less than 10%. Where adoption levels were high, the reported practice was mainly the manual-based planting basins in Malawi and Zimbabwe and ripline tillage in Zambia. The drivers of adoption of CA methods go beyond on-farm benefits or mass information awareness. Critical social, economic, institutional, and policy factors, many of which are systemic constraints to the agricultural sector broadly, are also impediments to progress in CA adoption. In some ways, progress in CA adoption may not be seen unless these sector-wide issues are resolved. In other cases, specific interventions targeted at CA promotion may provide the critical driving force. The project ‘Understanding and Enhancing Adoption of Conservation Agriculture in Smallholder Farming Systems of Southern Africa (ACASA),’ which is funded by the Norwegian Agency for Development Cooperation (Norad) and jointly implemented by the International Institute of Tropical Agriculture (IITA) and International Maize and Wheat Improvement Center (CIMMYT), aims to understand why previous efforts and investments to scale CA technologies and practices in southern Africa have not led to widespread adoption. The project is implemented in Malawi, Zambia, and Zimbabwe, where CA is part of major agricultural development policies. This report presents results from qualitative and quantitative surveys conducted by the ACASA project teams covering 24 districts, 305 villages, and 4,374 households across three countries in Southern Africa. The surveys were designed to understand incentives, drivers, and barriers to CA adoption and to assess prospects for mechanization across the region. Most of the past and ongoing interventions on CA in southern Africa have focused on promotion and technology delivery without a deeper understanding of the interactions between the socioeconomic, biophysical, and institutional constraints and opportunities for adoption of CA practices. For most resource-poor farmers, adoption of improved practices such as CA is primarily determined by their potential short-term benefits of crop yields, profits, risk avoidance, and livelihoods – and less so by longer-term improvements in soil properties or ecosystem services or other environmental services that are public goods in nature. The ACASA project was designed to go beyond bio-physical science (agronomic benefits) to encompass social and scaling science to understand not only the bio-physical performance but also the socio-economic and institutional drivers and barriers to adoption of CA technologies and practices.